Peningkatan Kemampuan Berjalan Bagi Penyandang Tunadaksa Di Yayasan Ypac Pangkal Pinang - Setiawan, Yudi; Ariksa, Jeri; Wijianti, Eka Sari; Saparin, Saparin; Taufiq, M Aries (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2025)
Efforts to develop assistive devices for children with disabilities at YPAC Foundation Pangkal Pinang, a school that provides education for children with special needs. This initiative is a form of commitment from the Mechanical Engineering Study Program in covering cooperation in the field of education at the YPAC Pangkal Pinang Foundation, where in 2023 the Mechanical Engineering Study Program at Bangka Belitung University has submitted a walking aid, but there is still much that needs to be developed from the device. The focus of this collaboration is aimed at children with disabilities, who have difficulty in mobility. Based on an evaluation by the UBB team with the General Chairperson of the YPAC Foundation, it was found that the device that we had submitted still had weaknesses in supporting walking training for children with disabilities, so that they still experienced difficulty and discomfort in experiencing walking. As a follow-up, the UBB Mechanical Engineering Team succeeded in updating a flexible walking aid that can be used by children of various ages, is safe when used and is expected to improve the mobility and quality of life of children with disabilities at the YPAC Pangkal Pinang Foundation.